Design and development of universal data logger for testing vehicle performance / Zuraidi Saad ... [et al.] - Saad, Zuraidi; Norma, Noor Hafizi; Md Saad, Azhar Efendi; Osman, Fairul Nazmie; Ahmad, Khairul Azman (Research Management Institute (RMI), 2009)
Monitoring car performance in terms of fuel consumption, velocity and other important parameters is crucial in order to ascertain whether a car is operating optimally. The purpose of this research is to design and develop a new data logger to monitor general car performance. Data has been collected via a wireless device attached to the car, which transmits information to the base station. The data logger (data acquisition processor) was developed based on an 8-bit Single-Chip Microcontroller. Speed, revs, fuel levels and temperature probes placed in the experimental car provided the required information. The information was then processed by the data acquisition processor before being transmitted to a computer via an RLM3000-Radio Link Modem. Laboratory results of the data logger for different speeds, revs and fuel levels are presented and discussed herein.